Epidemiology of stroke and transient ischemic attacks: Current knowledge and perspectives - Béjot, Y.; Daubail, B.; Giroud, M. (Revue neurologique, 2016)
Because of the growing size and aging of the world's population, the global burden of stroke is increasing dramatically. Current epidemiological data indicate that 16.9million people suffer a stroke each year, which represents a global incidence of 258/100,000/year, with marked differences between high- and low-income countries, and an age-adjusted incidence 1.5 times higher in men than in women. Although primary prevention has contributed to a decrease in stroke incidence in high-income countries, the so-called ‘epidemiological transition’ has led to an increase in incidence in middle-to-low-income countries as well. In addition, the incidence of ischemic stroke in young adults is on the rise, suggesting a need for specific preventative interventions in that age group. The number of stroke survivors almost doubled between 1990 and 2010, and has now reached 33 million people. According to epidemiological projections, this number will rise to 77 million by 2030. In France, the number of hospitalizations for an acute cerebrovascular event was about 138,000 in 2009, accounting for 3% of the total national health expenditure. Outcomes after stroke are frequently impaired by complications, including motor handicaps, dementia, depression, fatigue, and a high risk of early rehospitalization and institutionalization, with adverse consequences in terms of socioeconomic costs. In addition, there are 5.9 million stroke-related deaths worldwide every year. Finally, although many analytical epidemiological studies have considerably increased our knowledge of risk factors for stroke, the recent INTERSTROKE study provided evidence that 10 risk factors alone accounted for 88% of all strokes. Many of these risk factors are modifiable, which suggests that efforts should be made to promote interventions that aim to reduce the risk of stroke. A new ‘mass approach’ aiming to reduce the level of stroke risk factors in all people in a region, regardless of any given individual's level of risk, is currently still being developed. This interesting and innovative way to spread stroke awareness is based on the use of an internationally validated mobile-phone application that can calculate the risk of stroke for any given individual, and also contains a section to educate people on stroke warning symptoms and signs.